2022
DOI: 10.3390/pathogens11080883
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Uveal Inflammation and Viral Detection in 30 Cats with Feline Infectious Peritonitis

Abstract: Feline infectious peritonitis (FIP) virus is the most common infectious cause of uveitis in cats. Confirmatory diagnosis is usually only reached at postmortem examination. The relationship between the histologic inflammatory pattern, which depends on the stage of the disease, and the likelihood of detection of the viral antigen and/or RNA has not been investigated. We hypothesized that viral detection rate by either immunohistochemistry, in situ hybridization or RT-qPCR is dependent upon the predominant type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A study describing the ocular lesions in 15 cats with FIP found effusions in 13 cats and no effusion in only 2 cats [ 32 ], although other authors have found a low prevalence of effusions in cats with FIP-associated uveitis [ 244 ]. Ocular manifestations of FIP comprise anterior and/or posterior uveitis [ 15 , 35 , 45 , 233 , 243 ] ( Figure 8 , Figure 9 and Figure 10 ), with anterior uveitis being more common [ 245 ]. The uveitis is unilateral or bilateral [ 244 ].…”
Section: Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study describing the ocular lesions in 15 cats with FIP found effusions in 13 cats and no effusion in only 2 cats [ 32 ], although other authors have found a low prevalence of effusions in cats with FIP-associated uveitis [ 244 ]. Ocular manifestations of FIP comprise anterior and/or posterior uveitis [ 15 , 35 , 45 , 233 , 243 ] ( Figure 8 , Figure 9 and Figure 10 ), with anterior uveitis being more common [ 245 ]. The uveitis is unilateral or bilateral [ 244 ].…”
Section: Clinical Signsmentioning
confidence: 99%
“…Eyes enucleated as a result of uveitis-associated intractable glaucoma or pain can also be submitted for histopathology and IHC [ 174 ]. However, ocular tissues characterised by heavy plasmacytic inflammation in FIP are less likely to be IHC-positive for FCoV antigens [ 245 ]. The samples most likely to be useful are those that are affected by the disease process, and this can be guided by the results of diagnostic testing (e.g., imaging results, pyogranulomatous inflammation on FNA cytology) as well as clinical signs.…”
Section: Diagnosis Of Fipmentioning
confidence: 99%
See 1 more Smart Citation
“…Detecting an FIPV antigen within an efusion macrophage can be a good approach for viral antigen detection, and those involved mostly choose to target the nucleocapsid (N) protein due to its high-yield production in infected cells [2]. IHC is considered the "gold standard" for FIP diagnosis [5,13,43]. However, IHC is a time-consuming and complex procedure that requires specialized personnel and equipment [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…FIPV can efciently and continuously replicate in monocytes and macrophages [12]. Monocyte/ macrophage-tropic FIPV typically manifests as either efusive (wet form) or nonefusion (dry form) [13,14]. Te wet form is characterized by immune-mediated, fbrinous-granulomatous serositis, often with protein-rich efusions in the thoracic or abdominal cavities [15].…”
Section: Introductionmentioning
confidence: 99%